Tri Kaya Parisudha Sebagai Landasan Ajaran Etika Dan Moral Dalam Pendidikan Karakter Bagi Generasi Muda - Chandra Arini, Ni Putu; Yoga Pramana, Ida Bagus Kade (Jayapangus Press, 2021)
The younger generation is the generation that will bring change to a country. The ethics and morals of the younger generation need to be considered because they will become an example for future generations. Ethical and moral teachings need to be taught from an early age by parents, teachers and the surrounding community. In Hinduism, ethical and moral teachings are associated with Susila, Susila is good behavior carried out by humans. This teaches about the values regarding the good and bad actions that are done by someone in everyday life. The purpose of this study is to find out what teachings from Tri Kaya Parisudha are used as the basis of ethics and morals for the younger generation. The method used is qualitative method with literature study. The results of this study are that Tri Kaya Parisudha is used as the basis for the application of ethical teachings or Susila to be applied by the younger generation so that they are able to give birth to generations who have good morals and ethics in the surrounding community. The parts of Tri Kaya Parisudha's teachings are Manacika which means good thinking, Wacika which means saying good and right things and Kayika which means doing good which refers to the view of truth (dharma).